Coffee Farmers Empowerment by LMDH Argo Mulyo in Tambi Village, Kejajar District, Wonosobo Regency - Yuni Indarti (Indonesian Journal of Social Responsibility Review (IJSRR), 2022)
Empowerment is an effort made by the community, with or without the support of outsiders to improve their lives based on their own power, through power optimization efforts, as well as increasing their bargaining position, in other words, empowerment must put the strength of the community as the main capital and avoid the "engineering" of outsiders which often kills the independence of the local community. This study aims to find out and analyze the techniques for empowering coffee farming communities carried out by LMDH Argo Mulyo in Tambi Village, Kalijajar District, Wonosobo Regency, Central Java Province. The method used in this study is descriptive qualitative. The data collection techniques used are observation, interviews, and literature studies. Data analysis techniques are carried out by reducing data, presenting data, drawing conclusions, and verifying. Based on the results of the study, it shows that the implementation of empowerment carried out by LMDH Argo Mulyo for coffee farmers in Tambi Village, Wonosobo District, Central Java Province is going well covering 4 (four) aspects of empowerment, namely: Human Development, Business Development, Community Development, and Institutional Development.